Participatory Energy Transitions as Boundary Objects: The Case of Chile's Energía2050 - Urquiza, Anahí; Amigo, Catalina; Billi, Marco; Espinosa, Patricio (Frontiers in Energy Research, 2018)
This paper analyzes the use of “participatory futures” within the context of energy transition, paying special attention to the case of Chile's long-term energy policy. Our main aim is to question the role of “participation” in such a context and particularly, to decouple the operative function of participation from its normative function. Structurally, we argue that the construction of a joint vision of desired energy futures must be understood as a deliberate attempt at governing the energy transition by way of governing the expectations of the actors and systems involved in it. Participatory approaches can promote the co-construction of such energy futures in the form of a boundary-object, able to resonate with and provide a common reference to the actors participating in its creation. On the other hand, participatory approaches can also be a way to make transitions more democratic, subjecting it to a broader influence and control from the citizenship. These two functions of “participation” are always potentially at odds with one another. Democratizing the transition, in fact, would require producing plural, dynamical imaginaries that are responsive and accountable to the public. On the contrary, the need to make transitions governable may close-up such imaginaries and narrow-down the participatory efforts to foster their normalization and acceptability on the part of the most influential actors in the self-government of the transition. To refine and exemplify our proposal, we perform a qualitative, exploratory case study of Chile's E2050 energy policy. Our findings show that “participation” may indeed have been used in the case to align partially conflicting expectations around a collectively-defined boundary object which may then act as a form of contextual, anticipatory and polycentric governance of the transition. However, from a democratic perspective, E2050 appears as a tokenization of the public in support of a pre-eminently technical and monolithic vision enacted by the Energy Ministry and the Consultative Committee. Within this context, the actual influence of the public on the policy and the possibility for political contestation are much more questionable.